Gastric-floating microcapsules provide controlled and sustained release of multiple cardiovascular drugs - Lee, Wei Li (2013)
Floating polymeric microcapsules that simultaneously entrap multiple drugs were prepared using a solid/water/oil/water emulsion solvent evaporation method, based on harnessing interfacial phenomena and manipulation of the solvent removal process. The fabricated microcapsules exhibited excellent buoyancy in simulated gastric fluid and provided controlled and sustained release of multiple drugs for up to 24 h, thus revealing their potential as a rate-controlled oral drug delivery system.